MODEL DASHBOARD TERINTEGRASI MENGGUNAKAN SHNEIDERMAN’S INFORMATION SEEKING MANTRA UNTUK PENGOLAHAN DATA AKADEMIK, BEASISWA DAN TRACER STUDY - Sandy, Kurnia; Ardiyanto, Ardiyanto; Widyasari, Yohana Dewi Lulu; Arifin, Satria Perdana (Jurnal Komputer Terapan, 2025)
This study aims to develop an integrated data visualization dashboard that presents academic, scholarship, and tracer study information in real time at Politeknik Caltex Riau.(PCR). Data integration is carried out through an API Gateway within a Service-Oriented Architecture (SOA), ensuring that updates from each data source can be displayed immediately on the dashboard. To support effective and intuitive data exploration, the study applies Shneiderman’s Information Seeking Mantra, which consists of three main stages: overview first, zoom and filter, and detailson-demand. The resulting dashboard provides a comprehensive overview of key institutional indicators, offers interactive filtering features, and allows users to access detailed information such as student profiles, scholarship recipients, and alumni employment data. Performance testing using Apache JMeter demonstrates that most endpoints achieve response times below 500 ms, supporting the system’s capability for real-time data presentation. The findings indicate that the dashboard improves data monitoring efficiency, facilitates cross-domain analysis, and supports institutional decision-making based on accurate and timely information. Future enhancements may include the integration of predictive analytics and a more extensive user experience evaluation.